North America's Arctic Borders : A World of Change - Chater, Andrew; Nicol, Heather N. (Heather Nora), 1953- (Book collections on Project MUSE., 2021)
"Although part of a broader circumpolar world, North America's Arctic and sub-Arctic borders--and the establishment of new boundaries in the wake of significant, and regionally unique, change--are increasingly relevant in the broader, global world. Indeed, the Arctic reality has been dramatically reshaped by new territorial configurations and comprehensive land claims; increasing flows of international investment and trade focused upon resource industries and hydrocarbon extraction; the growing importance and role of sub-national entities, organizations, and Indigenous governments; shifting geopolitical interests; and existential challenges created by climate change and environmental security. This book demonstrates how North America's Arctic borders are being reshaped by globalization even as these borders are adjusting to new internal pressures such as devolution and the rise of sub-national territorial interests."--